2011
DOI: 10.1186/1742-2094-8-117
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine inhibits microglial activation by Aβ and confers neuroprotection

Abstract: BackgroundNeuroinflammation is an important contributor to the development of neurodegenerative diseases, including Alzheimer's disease. Thus, there is a keen interest in identifying compounds, especially from herbal sources, that can inhibit neuroinflammation. Amyloid-β (Aβ) is a major component of the amyloid plaques present in the brains of Alzheimer's disease patients. Here, we examined whether sinomenine, present in a Chinese medicinal plant, prevents oligomeric Aβ-induced microglial activation and confer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…Another suggested approach is to regulate the transporters responsible for modulation of extracellular glutamate, such as the cystine–glutamate transporter, which is profoundly upregulated in microglia that are activated by tat 150 . Unfortunately, no clinically available brain-penetrating inhibitors exist to test this hypothesis in patients, but preclinical development is underway 151,152 .…”
Section: Pathogenesis In Handmentioning
confidence: 99%
“…Another suggested approach is to regulate the transporters responsible for modulation of extracellular glutamate, such as the cystine–glutamate transporter, which is profoundly upregulated in microglia that are activated by tat 150 . Unfortunately, no clinically available brain-penetrating inhibitors exist to test this hypothesis in patients, but preclinical development is underway 151,152 .…”
Section: Pathogenesis In Handmentioning
confidence: 99%
“…As discussed above, rapamycin (at a low dose of 150 μg/kg) increased levels of M2-like anti-inflammatory cytokines IL-10 and TGFβ 105 . Sinomenine is a dextrorotatory morphinan analogue extracted from herbs used in traditional Chinese medicine 195,196 , and has long been used clinically for treating rheumatoid arthritis in China 197 . In vitro , sinomenine reduced levels of pro-inflammatory cytokines IL-1β, IL-6 and TNF in ICH-exposed BV-2 microglia 198 and increased levels of M2-like markers IL-10 and Arg1 in primary microglia exposed to erythrocyte lysate 199 .…”
Section: Clinical and Translational Implicationsmentioning
confidence: 99%
“…It has been indicated previously that oAβ possesses the ability to stimulate nitric oxide production from the activated BV-2 cells [22] or primary microglia [23]. Furthermore, it has been suggested that oAβ and fAβ stimulate differential activation on primary microglia [24], since oAβ is a stronger M1-inductor than fAβ [25].…”
Section: Discussionmentioning
confidence: 99%